First presentation of Ebstein’s anomaly in an 80-year-old female patient and unusual occurrence of psychiatric illness in her male offsprings - Shrestha, Umid Kumar; Sapkota, Subash; Thapa, Prakash (Journal of Advances in Internal Medicine, 2013)
An 80-year-old female Ebstein’s anomaly patient presented with palpitation and dyspnea of New York Heart Association class III. This is probably the eldest surviving Ebstein’s anomaly patient presenting for the first time with cardiac symptoms at the age of 80 years. She had four sons and two daughters, among whom the first three sons developed psychiatric disorders after 38 years of age, with one son committing suicide because of major depressive episode. This case is unique because of the late age of initial presentation with cardiac problem and the occurrence of psychiatric illness in the male offsprings of the patient. Journal of Advances in Internal Medicine 2013;02(01):21-23 DOI: http://dx.doi.org/10.3126/jaim.v2i1.7634